2005
DOI: 10.1109/tpwrd.2004.838635
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Measurements on Rotary Arcs in Hollow Polymeric Cylinders

Abstract: Rotary arcs in hollow polymeric cylinders have been monitored using electrical and optical techniques. The arcs burning within hollow cylinders were driven by electromagnetic forces. The arc voltage, current, dielectric strength below the arc gap, the optical emissions from the chamber were measured along with high-speed photography. The diameters of the hollow cylinders and magnitude of the applied magnetic field were varied. The arc voltage, especially the extinction peak prior to current zero, increased for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
2
1
Order By: Relevance
“…Therefore, higher interruption success rates with increasing ε were achieved by larger arc surface areas and weaker electric fields applied to the periphery of the gap. On the other hand, higher arc voltages for longer arc lengths in previous studies [37,38] were not observed in this research, because considerable stretch of arc lengths due to the arc looping did not occur in the 3 mm-short-gap arcs.…”
Section: Free Burningcontrasting
confidence: 82%
“…Therefore, higher interruption success rates with increasing ε were achieved by larger arc surface areas and weaker electric fields applied to the periphery of the gap. On the other hand, higher arc voltages for longer arc lengths in previous studies [37,38] were not observed in this research, because considerable stretch of arc lengths due to the arc looping did not occur in the 3 mm-short-gap arcs.…”
Section: Free Burningcontrasting
confidence: 82%
“…EVERAL evolving aspects of high voltage current interruption which are currently commanding attention include the interruption of direct currents (D.C.) rather than alternating currents (A.C.) and the drive towards avoiding the use of sulfur hexafluoride (SF6) gas as an arc quenching agent because of its potential for causing Global Warming [1]. Meanwhile, technology based upon the evolution of various forms of electromagnetic control of electric arcs has been investigated over several years with potential for current interruption applications [1][2][3]. Examples of particular forms of such devices include, as well, an electric arc convolute rotating around a polytetrafluoroethylene (PTFE) cylinder housing a magnetic field (B-field) producing coil, a similar arrangement with an outer PTFE cylinder with the arc rotating in the annular gap between the outer and inner PTFE cylinders etc.…”
Section: Introductionmentioning
confidence: 99%
“…With the concentrator inner radius R3, maximum secondary current2 i in the flux concentrator (Fig. 4), and permeability of free space o is the effective inductance of the flux concentrator, is the self-inductance of the central high filed region [7], i 1 is a primary current through the arc and B-field coil (which are connected in series) and '  is the transfer inductive energy loss between the B-field producing coil and the central high field region (b = 0.03m, Fig.…”
mentioning
confidence: 99%